The Effect Of Brain Gym With The Level Of Stress On Elders In Panti Sosial Lanjut Usia Potroyudan Jepara - Alvita, Galia Wardha; Huda, Sholihul (Universitas Islam Lamongan, 2020)
Along with the increasing number of elderly people in Indonesia, it will cause quite complex problems, both physical and psychosocial problems. The most common psychosocial problem in the elderly is stress. Efforts to overcome the problem of tress in the elderly are brain exercise therapy. This study aims to determine the effect of brain exercise therapy on stress levels in the elderly. The research design used by the researcher was Quasy Experiment with pre-post test design. This study used a sample of 30 respondents. The sampling technique used is purposive sampling. Based on the analysis test using the Wilcoxon Signed Rank Test, it shows a p-value of 0,000, so there is an effect of brain exercise therapy on stress levels in the elderly. This study provides general information related to the management of stress disorders in the elderly using brain exercise therapy. In addition, the findings from this study are expected to provide advice for nursing service providers, especially in nursing homes. local area so that they can carry out brain exercise therapy as a program to improve the health of the elderly.Â Keywords: Â